STUDI KEBIJAKAN PENERAPAN BAHASA, BUDAYA DAN SEJRAH BEKASI SEBAGAI MUATAN LOKAL DI SEKOLAH - Andi Sopandi (Makna: Jurnal Kajian Komunikasi, Bahasa, dan Budaya, 2012)
This paper discusses the implementation of language ability, culture and history as local content in schools curriculum in Bekasi. The educational development of local-content character often faces the polemics and the proper methods in implementating it. It also includes efforts to develop local content such as local history and culture of Bekasi. Therefore, it takes effort to make stages in implementing local-content curriculum systematically, starting from the problem identification, enrichment of local-content curriculum, until the mechanism of the right policy for the purpose to build generation with local and national content-character going hand in hand.